Tabuik Pariaman: A Formal Analysis - Ara Salsabila Putri; Elvis Elvis; Jufrinaldi Jufrinaldi (Institut Seni Indonesia Padang Panjang, 2026)
This study aims to examine the form and physical structure of Tabuik Pariaman, a cultural heritage of the Minangkabau community in West Sumatra, Indonesia. Employing a descriptive qualitative approach, data were collected through field observations, semi-structured interviews, and a comprehensive literature review. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, while the investigation of form adopted Feldman’s formal analysis approach to identify the visual elements and compositional principles that underlie Tabuik's structure. The symbolic meanings embedded within each component were interpreted through Geertz’s perspective of symbolic anthropology. The findings reveal that Tabuik comprises several principal elements: Burak, Bungo Salapan, Gomaik, Biliak-Biliak, Jantuang-Jantuang, Pasu-Pasu, Tonggak Atam, and Tonggak Miriang. These components integrate geometric and organic forms to produce a harmonious, balanced, and monumental visual composition. Beyond their constructive functions, each element embodies symbolic meanings associated with spirituality, leadership, fertility, the unity of customary law and religion, and the community’s collective memory of the Karbala tragedy. The study confirms that Tabuik should be understood not merely as a visual cultural artifact but also as a medium through which the people of Pariaman express their cultural identity by integrating historical, aesthetic, and symbolic values. Therefore, its preservation and systematic documentation remain essential to Indonesia’s cultural heritage.